Land, Environmental Externalities and Tourism Development - Javier Lozano Ibá\~nez; Javier Rey-Maquieira Palmer; Carlos Mario Gómez Gómez (Fondazione Eni Enrico Mattei (FEEM), 2004)
In a two sectors dynamic model we analyze the process of tourism development based on the accumulation of capital (building of tourism facilities) and the reallocation of land from traditional activities to the tourism sector. The model incorporates the conflict between occupation of the territory by the tourism facilities, other productive activities and availability of cultural, natural and environmental assets that are valued by residents and visitors. We characterize the process of tourism development in two settings: the socially optimal solution and a situation where the costs of tourism expansion are external to the decision makers, where externalities on residents as well as intraindustry externalities are considered. Regarding the optimal solution, we show that it is optimal to limit tourism expansion before it reaches its maximum capacity even in a context where the economic attractiveness of tourism relative to other productive sectors rise continuously. However, in this context and when all the costs of tourism development are externalities the only limit to tourism quantitative expansion is its maximum capacity determined by the availability of land. Finally, we show that excessive environmental degradation from the future generations' point of view is not a problem of discounting the future but rather a problem of externalities that affects negatively the current and future generations.
Keywords: O41; Q24; 330; Intertemporal land allocation; Structural economic change; Tourism industry; Tourismus; Externer Effekt; Landnutzung; Allokation; Dynamisches Gleichgewicht; Theorie